High resolution analysis of GeH4 in the dyad region: Ro-vibration energy structure of 70GeH4 and line strengths of MGeH4 (M = 70, 72, 73, 74, 76); Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 236 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Kuznetsov A. V. Alexey Valerevich; Sydow C. Christian; Bauerecker S. Sigurd (2019, 2019)
Title screen